Recombinant yeast for production of the pain receptor modulator nonivamide from vanillin - Muratovska, Nina; Carlquist, Magnus (Frontiers in Chemical Engineering, 2023)
We report on the development of a method based on recombinant yeast Saccharomyces cerevisiae to produce nonivamide, a capsaicinoid and potent agonist of the pain receptor TRPV1. Nonivamide was produced in a two-step batch process where yeast was (i) grown aerobically on glucose and (ii) used to produce nonivamide from vanillin and nonanoic acid by bioconversion. The yeast was engineered to express multiple copies of an amine transaminase from Chromobacterium violaceum (CvTA), along with an NADH-dependent alanine dehydrogenase from Bacillus subtilis (BsAlaDH) to enable efficient reductive amination of vanillin. Oxygen-limited conditions and the use of ethanol as a co-substrate to regenerate NADH were identified to favour amination over the formation of the by-products vanillic alcohol and vanillic acid. The native alcohol dehydrogenase ADH6 was deleted to further reduce the formation of vanillic alcohol. A two-enzyme system consisting of an N-acyltransferase from Capsicum annuum (CaAT), and a CoA ligase from Spingomonas sp. Ibu-2 (IpfF) was co-expressed to produce the amide. This study provides proof of concept for yeast-based production of nonivamide by combined transamination and amidation of vanillin.